Representações sociais de sírios e libaneses em Corumbá, MS: comércio, casamento e cemitério - (:unkn) unknown (Revista Transporte y Territorio, 2016)
Para acceder al Artículo utilice el link: http://revistascientificas.filo.uba.ar/index.php/rtt/article/view/2867
This article aims to understand how the Syrian and Lebanese representations through the graves which socially represent the immigration expressed in Santa Cruz cemetery in Corumbá, MS, Brazil. The clearest evidence is that they successfully reproduced trajectories achieved by wealthier social layers. Such trajectories were to consolidate the commercial operations and subsequently arrange alliances through marriage among people of local families who had social prominence. We start from recognition that this custom was not trodden by all immigrants of the city, that is, only a few of them could succeed. We intend to discuss here the successful individuals who achieved significant results while living in Corumbá. The methodology used was the survey of documentary sources in the collections which are available in the city.
Este artigo busca entender como os imigrantes sírios e libaneses construíram representações sociais expressas no cemitério Santa Cruz em Corumbá, MS, Brasil. As evidências mais claras são de que eles reproduziram trajetórias de sucesso alcançado por camadas sociais mais abastadas. Tal trajetória consistia em consolidar a atuação mercantil e, posteriormente, realizar o matrimônio com pessoas de famílias locais, que possuíssem destaque social. Partimos de um reconhecimento de que esse caminho não foi trilhado por todos os imigrantes chegados àquela cidade, ou seja, apenas uma parcela deles conseguiu obter êxito. Trataremos aqui dos exitosos que obtiveram resultados expressivos em suas permanências em Corumbá. A metodologia utilizada foi a de levantamento de fontes documentais nos acervos disponíveis naquela cidade.
Fil: Machado de Oliveira, Marco Aurélio. Universidade Federal de Mato Grosso do Sul; Brasil.
Fil. Monseff Junqueira, Nathalia. Universidade Federal de Mato Grosso do Sul; Brasil.
Keywords: immigrants; syrians and lebanese; cemetery; social representations; inmigrantes; sirios y libaneses; cementerio; representaciones sociales